2016
DOI: 10.15361/1984-5529.2016v44n4p575-583
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of sulfentrazone herbicide in soils with different textures

Abstract: The objective of this study was to evaluate the leaching potential of sulfentrazone herbicide through bioindicator plants after the occurrence of natural rainfall in soils with clayey and sandy textures. The experimental design was completely randomized in a 3 x 8 factorial with four replications, with three levels of rainfall (30-40, 60-80 and 100-120 mm) and eight depth of soil profile (0-3, 3-6, 6-9, 9-12, 12-15, 15-20, 20-25 and 25-30 cm). The collections of samples occurred after sulfentrazone application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…High doses of S-metolachlor applied to sandy soils and soils with low organic matter can cause injury to sunflower (Brighenti et al, 2013). In addition, the leaching potential of S-metolachlor is strictly correlated with rainfall (Inoue et al, 2010 The adsorption of sulfentrazone to the soil is also influenced by pH and organic matter content (Silva Júnior et al, 2016). The value of organic matter was lower in Valença (2.8 dag kg -1 ) than in Coronel Pacheco (3.3 dag kg -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…High doses of S-metolachlor applied to sandy soils and soils with low organic matter can cause injury to sunflower (Brighenti et al, 2013). In addition, the leaching potential of S-metolachlor is strictly correlated with rainfall (Inoue et al, 2010 The adsorption of sulfentrazone to the soil is also influenced by pH and organic matter content (Silva Júnior et al, 2016). The value of organic matter was lower in Valença (2.8 dag kg -1 ) than in Coronel Pacheco (3.3 dag kg -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another fraction (250g) of each treatment was placed in pots of 300 cm 3 capacity, where the bioindicator Sorghum bicolor was planted. S. bicolor was selected as an indicator of sulfentrazone residues in soil based on several studies (Faustino et al, 2015, Silva Junior et al, 2016, Madalão et al, 2017 that confirmed the high sensitivity of this species to sulfentrazone.…”
Section: Soilmentioning
confidence: 99%
“…This technique is based on the use of plants that are sensitive to the tested herbicides, so that the presence of residues in the soil is evidenced by changes in physiological and morphological characteristics of the key-plant species. In the literature, several studies involving bioassays for determination of leaching of herbicides such as amethrin (Silva et al, 2012), sulfentrazone (Silva Junior et al, 2016), imazethapyr, imazapyque and imazapyr (Bundt et al 2014) have been reported. On the other hand, to test the efficiency of this method, it would be interesting to compare it with already consolidated methods such as HPLC.…”
Section: Introductionmentioning
confidence: 99%